Can CSR engagement and strong internal control enhance sustainable corporate growth? Evidence from Chinese listed companies - Oleh Pasko; Li Zhang; Yarmila Tkal; Mykola Hordiyenko; Liubov Popova; Yulia Abraham (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2021)
Adopting agency theory and stakeholder theory,the paper examines the relationship between corporate social responsibility (CSR) and the strength of internal control (IC) alone, as well as combined on the sustainable corporate growth of Chinese listed companies. By examining through regression analysis using Stata16 the sample of 17,294 firm-year observations of China's A-share listed companies over the period 2010 to 2018,we show that CSR and IC are both beneficial to companies' sustainable growth. The findings manifest a significant association, both in the event of separate testing of the two actors (CSR and IC) and in the case of the coupled effect thereof, on sustainable corporate growth (SCG). We show that CSR and IC allow harmonizing actual growth with internal resources available and that CSR and IC both enhance the company's sustainable growth rate. We document that CSR and IC increase thethreshold enabling companies to grow internally without resorting to further use of sparse limited resources. We argue that the CSR and IC can realize the interactive influence on the sustainable growth of the enterprise, and then produce the synergy effect. As a whole, our findings supply a novel implication that the extent of CSR and IC can enhance sustainable corporate growth.
Keywords: 330; corporate social responsibility; internal control; sustainable corporate growth; sustainable company growth; Chinese listed companies